Integrating Gamification in LMS to Enhance Self-Directed Learning and Learning Outcomes in Social Education - Malawi, Ibadullah; Fajriyah, Izzatul (Journal of Teaching and Learning, 2026)
The integration of gamification in learning management systems (LMS) has gained traction as a strategy to enhance learning outcomes and promote self-directed learning (SDL); however, existing studies often lack a comprehensive understanding of its specific impacts on student engagement and SDL behaviours in the context of social education. Addressing this gap, this study aims to explore the effects of gamified LMS on learning outcomes and SDL dimensions, self-management, self-motivation, and self-control. A sequential mixed-methods approach was employed, involving 60 undergraduate students in the social education program at Universitas Negeri Surabaya, Indonesia. Quantitative data were collected through pre- and post-tests on learning outcomes and an SDL questionnaire, while qualitative insights were obtained via in-depth interviews. Findings revealed significant improvements in learning outcomes, with students demonstrating better mastery of course content. In terms of SDL, notable gains were observed in self-motivation and self-control, although challenges persisted in maintaining consistent self-management among some participants. Negative insights included technical difficulties and varying levels of digital literacy, both of which affected engagement. These findings suggest that gamified LMS can effectively enhance educational experiences but require tailored support to address individual learner needs. Implications include the need for adaptive gamification designs and instructor facilitation to maximize SDL behaviours.